Divergence of Languages as Resources for Theorizing - Thi Hong Nhung Nguyen (MDPI AG, 2017)
This paper investigates the potential of conceptual divergences within and between languages for providing intellectual resources for theorizing. Specifically, it explores the role of multilingual researchers in using the possibilities of the plurality of intellectual cultures and languages they have access to for theorizing International Service Learning (ISL). In doing so, this investigation of conceptual divergence within/between languages shows how it is possible for multilingual researchers to extend their capabilities for theorizing; to bring forward possibilities for theorizing ISL in languages other than English; and to potentially bring new perspectives to a field of enquiry which lays claim to being "international". The process of developing the capability for theorizing begins by exploring the divergence in languages of key concepts. In this instance, the analysis focuses on the English concept of "service learning" which is rendered in Tiếng Việt (i.e., Vietnamese language) as học tập phục vụ cộng đồng. The analysis of the conceptual divergence represented by these Tiếng Việt concepts opens up insights into ways of developing the capabilities that multilingual researchers have for theorizing. In effect, this paper contributes to the knowledge about the options multilingual researchers have for using their full linguistic repertoire for the purpose of theorizing. The study has significant implications for multilingual education, multilingual research and theorizing ISL in universities which privilege English-only monolingualism.